Yupingfeng San Inhibits NLRP3 Inflammasome to Attenuate the Inflammatory Response in Asthma Mice - Liu, Xue; Shen, Jiawen; Fan, Danping; Qiu, Xuemei; Guo, Qingqing; Zheng, Kang; Luo, Hui; Shu, Jun; Lu, Cheng; Zhang, Ge; Lu, Aiping; Ma, Chaoying; et al. (Frontiers in Pharmacology, 2017)
Yupingfeng San (YPFS) is a representative Traditional Chinese Medicine (TCM) formula with accepted therapeutic effect on Asthma. However, its action mechanism is still obscure. In this study, we used network pharmacology to explore potential mechanism of YPFS on asthma. Nucleotide-bindling oligomerization domain (NOD)-like receptor pathway was shown to be the top one shared signaling pathway associated with both YPFS and asthma. In addition, NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome was treated as target protein in the process of YPFS regulating asthma. Further, experimental validation was done by using LPS-stimulated U937 cells and ovalbumin (OVA)-sensitized BALB/c mice model. In vitro experiments showed that YPFS significantly decreased the production of TNF-α and IL-6, as well as both mRNA and protein levels of IL-1β, NLRP3, Caspase-1 and ASC in LPS-stimulated U937 cells. In vivo experiment indicated that YPFS treatment not only attenuated the clinical symptoms, but also reduced inflammatory cell infiltration, mucus secretion and MUC5AC production in lung tissue of asthmatic mice. Moreover, YPFS treatment remarkably decreased the mRNA and protein levels of IL-1β, NLRP3, Caspase-1 and ASC in lung tissue of asthmatic mice. In conclusion, these results demonstrated that YPFS could inhibit NLRP3 inflammasome components to attenuate the inflammatory response in asthma.